Lived experience as a unit of analysis for the study of learning. (December 2021) - Dieumegard, G.; Nogry, S.; Ollagnier-Beldame, M.; Perrin, N.
Abstract: To study individual features of a learning activity entangled in a material and social environment, we adopt lived experience as a fundamental unit of analysis. Defined as an ongoing process which is known "from within" by individuals, lived experience derives from the phenomenological tradition and is rooted in the enactive approach of cognition. As such, lived experience appears to be active and passive, holistic, situated in a complex temporality, and partly pre-reflective. The study of lived experience of learners requires the researcher to adopt a second-person perspective in which s/he constitutes descriptions of lived experience through a relational process. We present two second-person methods for collecting data: explicitation and self-confrontation interviews. Two case studies illustrate the implementation of these methods: the first focuses on sensorial experience in swimming lessons, and the second concerns understanding in teacher training. Endorsing lived experience as a unit of analysis allows thinking anew the consideration of the individual into socio-cultural approaches of learning.